International Economic Policy Review, Volume 1 - Masson, Paul.; Gotur, Padma; Lane, Timothy (Washington, D.C. : International Monetary Fund, 1999)
This series aims to make available to the general public and to economic policy practitioners, a selection of policy papers prepared by the staff of the International Monetary Fund. Papers in the International Economic Policy Review will offer specific policy-relevant analysis, but at a relatively non-technical level. These papers are intended to provide analytical background for IMF-supported programs and more generally to shed light on a range of policy choices facing ministries and central banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet